DYNAMICS OF SOCIAL INTERACTION BETWEEN BOARDING HOUSE RESIDENTS AND THE LOCAL COMMUNITY IN MAJENE REGENCY - Rahmatullah; Husniah; Muhammad Gaus (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study analyzes the dynamics of social interactions between boarding house residents and the local community in Majene Regency, West Sulawesi. The growth of boarding houses as a consequence of the increasing number of incoming students has created a new social space that brings together diverse cultural backgrounds. Using a qualitative phenomenological approach, this study explores the experiences of boarding house students, boarding house owners, and the local community in building social relationships, adapting to local norms, and managing potential conflicts. The results show that social interactions occur across a broad spectrum, ranging from associative forms such as accommodation and cooperation to dissociative forms such as controversy and value conflicts. Factors influencing the dynamics of interactions include cultural background, communication intensity, the role of boarding house managers, community leaders, and the duration of students' stay. Social capital in the form of networks, trust, and norms has proven to be an important instrument in facilitating student adaptation while strengthening social cohesion with the local community. This study confirms that boarding houses function not only as temporary housing but also as social institutions that play a role in the process of cultural and social integration in Majene. These findings contribute to the sociological study of social interaction and social capital and provide a basis for local policies to manage boarding houses more inclusively.